2018
DOI: 10.3390/ijms19061658
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Signatures in Gastric Cancer Prognosis

Abstract: Gastric cancer is one of the most common malignancies worldwide and it is a fourth leading cause of cancer-related death. Carcinogenesis is a multistage disease process specified by the gradual procurement of mutations and epigenetic alterations in the expression of different genes, which finally lead to the occurrence of a malignancy. These genes have diversified roles regarding cancer development. Intracellular pathways are assigned to the expression of different genes, signal transduction, cell-cycle superv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 116 publications
0
47
1
3
Order By: Relevance
“…Gastric cancer (GC) occurs in the mucosa of the stomach and is the most common malignancy of the digestive system. [ 1 ] According to the World Health Organization and the International Agency for Research on Cancer's 2018 Global Cancer Statistics Report, GC mortality ranks third among global malignancies. [ 2 ] The incidence and mortality of GC in China are notably higher than those in western countries.…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer (GC) occurs in the mucosa of the stomach and is the most common malignancy of the digestive system. [ 1 ] According to the World Health Organization and the International Agency for Research on Cancer's 2018 Global Cancer Statistics Report, GC mortality ranks third among global malignancies. [ 2 ] The incidence and mortality of GC in China are notably higher than those in western countries.…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer (GC) is one of the most common digestive malignancies. 1 The global cancer statistics reports of the World Health Organization and the International Agency for Research on Cancer in 2018 reported that the death rate of GC ranked third among all malignant tumors worldwide. 2 In China, both the morbidity and mortality of GC were obviously higher than western countries.…”
Section: Introductionmentioning
confidence: 99%
“…Metastasis that mainly occurs due to peritoneal dissemination is considered as the leading cause of mortality in gastric adenocarcinoma patients. This process is accompanied with alterations in the biology and molecular characteristics of the tumour and, therefore, identification of the biomarkers underlying cell migration and metastasis is of utmost importance in diagnosis, therapeutic and prognosis …”
Section: Discussionmentioning
confidence: 99%
“…This process is accompanied with alterations in the biology and molecular characteristics of the tumour and, therefore, identification of the biomarkers underlying cell migration and metastasis is of utmost importance in diagnosis, therapeutic and prognosis. 28,29 To isolate a panel of diffuse GC cell reactive antibodies from Tomlinson I library, we selected two gastric adenocarcinoma cell lines, MKN45 and AGS, as representatives for Lauren's diffuse and intestinal subtypes, and applied a subtractive-based selection procedure. To reduce the number of irrelevant phage-scFvs and increase specific binders, we performed four rounds of biopanning each consisting of three negative steps with NIH-3T3 and AGS followed by one step of positive selection on MKN-45.…”
Section: Discussionmentioning
confidence: 99%